Geometallurgy – Bridging the Gap between Mine and Mill: a Case Study of the DeGrussa Geometallurgy Program - C Butler; R Dale; S Robinson; A Turner (The Australasian Institute of Mining and Metallurgy, 2016)
"Sandfire Resources NL- (‘Sandfire’) DeGrussa definitive feasibility study (DFS) identified geometallurgy as a major factor in achieving optimum plant performance at the DeGrussa mine. A geometallurgical initiative was created to proactively investigate this issue, and a key initial achievement was the 2013 paper by Condon et al (2013) on developing a working geometallurgical model from first principles. Significant advancements in Sandfire’s geometallurgical understanding since that publication now shape how information is presented and communicated.The main geometallurgical parameters so far identified as critical factors affecting plant performance are Cu:S ratio, iron sulfide mineralogy, talc carbonate content and sphalerite content. Apart from specific mill strategies, geometallurgical issues have been managed through communication between departments and strategic run-of-mine (ROM) pad management.This paper uses the current theories of geological evolution of the volcanogenic massive sulfide (VMS) deposit at DeGrussa, to discuss the variability between the orebodies C1, DeGrussa (sea floor mounds) and C4, C5 (sub-sea floor replacement) to highlight the different issues each orebody is expected to encounter when processing.A zone of altered low-grade mineralisation surrounds the main orebodies at DeGrussa, referred to as a halo. Talc minerals are often patchy within this halo and often cause significant recovery issues during processing. This halo has been successfully modelled using MgO as a proxy. The ability to model the talc material assists with both identifying potentially problematic zones for processing and geological interpretation of the ore deposits evolution.Early in geometallurgy studies at DeGrussa it became apparent that it would be useful to identify processing performance prior to mining. This necessitated the incorporation of specific sulfide species into the mining block model. These attributes are interpolated from the logged sulfide estimates allowing a clear picture of the abundance of each mineral type within a defined area.In conjunction with the block model a geometallurgical factor (GMF) graph was developed, identifying sulfide mineralogy based upon mineral assays. These two recent additions to the model provide a clear picture of the nature of the ore sources that will be presented to the processing plant.The future of geometallurgy at DeGrussa will see these tools used to aid mine scheduling with a view to further improve processing recoveries.CITATION:Butler, C, Dale, R, Robinson, S and Turner, A, 2016. Geometallurgy – Bridging the Gap between Mine and Mill: a Case Study of the DeGrussa Geometallurgy Program, in Proceedings The Third AusIMM International Geometallurgy Conference (GeoMet) 2016, pp 77–88 (The Australasian Institute of Mining and Metallurgy: Melbourne)."